2022
DOI: 10.1136/bmj.o2551
|View full text |Cite
|
Sign up to set email alerts
|

Improving adolescent wellbeing is an urgent global priority

Abstract: A BMJ collection urges decision makers to reverse decades of neglect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Additionally, not many participants in such studies had distress symptoms, meaning that we tend to focus on an already relatively healthy population, while lacking more clinical samples. Since the mental health of youths should be one of the societal priorities [98,99], we have to make a further effort to narrow down key factors that could serve as risk and/or protective factors and find new ways to introduce them into everyday mental health practices, especially considering the long-term consequences of the pandemic. As Wu at al.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Additionally, not many participants in such studies had distress symptoms, meaning that we tend to focus on an already relatively healthy population, while lacking more clinical samples. Since the mental health of youths should be one of the societal priorities [98,99], we have to make a further effort to narrow down key factors that could serve as risk and/or protective factors and find new ways to introduce them into everyday mental health practices, especially considering the long-term consequences of the pandemic. As Wu at al.…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…Covid-19 has essentially reversed gains in gender equality, widening socioeconomic, educational, and health inequalities for women and the world’s 1.8 billion young people (aged 10-24 years). 3 4 During the pandemic and its aftermath, women and girls carried an unequal burden of care, faced increased gender based violence, and endured severe disruptions to their health and educational services. 3 According to Unesco, the pandemic risked more than 11 million girls not returning to school, with those in LMICs at particular risk.…”
mentioning
confidence: 99%
“… 8 9 Globally, one in seven adolescents experiences a mental health condition (around 80% of whom are in LMICs). 4 The latest World Mental Health Report indicated a 25% increase in global rates of anxiety and depression in the first year of the pandemic, with further evidence confirming a higher prevalence and increased risk among youth, especially girls, those with disabilities, those living in emergency and conflict affected settings, and indigenous, sexual, and ethnic minorities. 10 Moreover, a global survey on climate anxiety among young people found that more than 60% felt extremely worried and 84% moderately worried about climate change, with high correlation between anxiety and perceived inadequate governmental response to the climate crisis.…”
mentioning
confidence: 99%